Optimal Investment Strategies under Demand and Tax Policy Uncertainty - Hjalmar Boehm; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we offer an analysis of the effects of uncertainty about future tax policy on irreversible investment. The main message of the paper is that investment is not much affected by the degreee of tax policy uncertainty. This is true regardless of whether random tax changes are determined endogenously or exogenously. The paper therefore indicates that reducing tax policy uncertainty is probably no magic bullet to increase private investment spending
Keywords: 330; Investment; uncertainty; irreversibility; taxation